2009
DOI: 10.1103/physrevlett.102.025701
|View full text |Cite
|
Sign up to set email alerts
|

Criticality of Tuning in Athermal Phase Transitions

Abstract: We experimentally address the importance of tuning in athermal phase transitions, which are triggered only by a slowly varying external field acting as tuning parameter. Using higher order statistics of fluctuations, a singular critical instability is detected for the first time in spite of an apparent universal self-similar kinetics over a broad range of driving force. The results as well as the experimental technique are likely to be of significance to many slowly driven non-equilibrium systems from geophysi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
44
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 33 publications
5
44
0
Order By: Relevance
“…The effect of drive rates has been probed in our earlier work as well 18 and Fig.8(a) shows very similar results. To understand the second spectral characteristics (i.e.…”
Section: Drive Rate Effectssupporting
confidence: 77%
See 2 more Smart Citations
“…The effect of drive rates has been probed in our earlier work as well 18 and Fig.8(a) shows very similar results. To understand the second spectral characteristics (i.e.…”
Section: Drive Rate Effectssupporting
confidence: 77%
“…Similar correlation of non-Gaussian electrical noise and first order structural phase change was observed in NiTi thin film as well 18 , outlining an excellent kinetic detector of structural phase transition. The NGC in resistivity noise has been attributed to emergence of a long range correlation in many systems with electronic 24 , structural 18 or magnetic 25 phase transitions. The magnitude of σ (2) is directly associated to a correlation length ξ which, in case of martensitic alloys, characterizes the range of elastic correlation in the system.…”
Section: A Resistivity Fluctuations and Statisticssupporting
confidence: 66%
See 1 more Smart Citation
“…Experiments on a wide variety of systems like doped silicon [13], metal nanowires [14], shape memory alloys [15,16], disordered magnetic alloys [17] etc. have shown that time dependent fluctuations (noise) in physical observables exhibit a strong non-Gaussian behavior due to the presence of long-range correlations originating from coulomb forces, internal strain fields or magnetic interactions.…”
mentioning
confidence: 99%
“…The second spectrum is a sensitive technique to estimate the presence of non-Gaussian component (NGC) in the resistance fluctuations [15,31,32]. The experimental scheme employed to measure the second spectrum is shown in Fig.…”
mentioning
confidence: 99%